Kounis syndrome: acute myocardial injury triggered by ant bite-induced anaphylaxis - Omar Altermanini (22391776) (2025)
Anaphylaxis triggered by insect bites is well-documented, but its association with acute myocardial injury (AMI) is rare. We report a case of Kounis syndrome, where an ant bite induced anaphylaxis and myocardial injury. A 47-year-old diabetic male presented with anaphylaxis following an ant bite, exhibiting hypotension, respiratory distress, and wheezing. Electrocardiography revealed transient widespread ST depression and ST elevation in lead aVR, a pattern reflecting global ischemia, which is uncommon in Kounis syndrome. Treatment with intramuscular adrenaline stabilized his condition. Peak troponin T levels were 1306 ng/l. Coronary angiography and cardiac MRI were unremarkable, ruling out significant coronary artery disease. The patient was diagnosed with Kounis syndrome and discharged with an EpiPen and instructions for anaphylaxis management. This case highlights the potential for ant bites to trigger anaphylaxis-associated myocardial injury, emphasizing the importance of prompt diagnosis and management of Kounis syndrome in similar scenarios. Other Information Published in: Oxford Medical Case Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/omcr/omaf020